2021
DOI: 10.2147/ccid.s327870
|View full text |Cite
|
Sign up to set email alerts
|

Dermatologists’ Knowledge and Attitude Toward Isotretinoin Ocular Side Effects in Egypt

Abstract: Aim The FDA approved isotretinoin for moderate and severe nodulo-cystic acne, in which it proved effective. However, this misled the dermatologists into using isotretinoin for mild cases as well. This misuse increased the risk of developing adverse effects, especially on the ocular system. These adverse effects vary from mild reversible eye dryness to severe irreversible loss of night vision. Also, it causes contact lens intolerance and corneal ulcer on top. Both ophthalmologists and dermatologist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 12 publications
(35 reference statements)
0
1
0
Order By: Relevance
“…Nearly all dermatologists prescribed lubricant eye drops routinely for patients in ISO treatment in Egypt. 55 Villani et al 30 also found that patients might experience dry mucous membranes, such as eyes, nose, and mouth, when the dose was too high for them. This might be because systemic ISO administration altered the function and structure of meibomian glands and inhibited lipid production, resulting in rapid tear evaporation.…”
Section: Resultsmentioning
confidence: 99%
“…Nearly all dermatologists prescribed lubricant eye drops routinely for patients in ISO treatment in Egypt. 55 Villani et al 30 also found that patients might experience dry mucous membranes, such as eyes, nose, and mouth, when the dose was too high for them. This might be because systemic ISO administration altered the function and structure of meibomian glands and inhibited lipid production, resulting in rapid tear evaporation.…”
Section: Resultsmentioning
confidence: 99%
“…In the Jordanian context, it seems necessary for dermatologists to sharpen their understanding of isotretinoin, including its potential side effects and associated conditions, by raising the level of awareness of potential side effects, and the urgent need to take the necessary precautions for side effects. In this study, only a few of the participating dermatologists advised the patients not to use contact lenses (n=6, 4.08%), and few prescribed moisturizing eye drops (n=17; 11.57%); in any case, the most important side effect of the drug is teratogenicity [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…The results showed that 73.33% of children in Group C experienced acne scars and post-acne hyperpigmentation [ 22 ]. Elshafie et al [ 21 ] reported that among 103 Egyptian dermatologists, 92.8% of them sometimes prescribed isotretinoin alone for moderate to severe nodulo-cystic acne, 4.5% rarely prescribed it (only for a case with primary comedone), and 2.7% always prescribed the drug for all acne types. With regard to knowledge of ocular side effects, 94.6% of dermatologists reported their knowledge and 5.4% did not know about them [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…A cross-sectional study in Egypt found that 94.6% of dermatologists were aware of ocular side effects, 91.1% informed patients about the drug's adverse effects and 74.8% knew about contact lens intolerance. Most dermatologists routinely prescribed lubricant eye drops and 56.8% referred patients to an ophthalmologist [ 21 ]. This study’s hypothesis is that there is a lack of sufficient knowledge about the ocular side effects of isotretinoin among dermatologists in Saudi Arabia.…”
Section: Introductionmentioning
confidence: 99%